IDENTIFICATION AND CHARACTERIZATION OF ANCHOVY (Stolephorus commersonnii) PRODUCED IN TANJUNG TIRAM VILLAGE BATU BARA REGENCY - Rexi, Daniel; Pintauli, Sondang; Dalimunthe, Aminah; Nasri, Nasri (Talenta Publisher, 2025)
Anchovy is a widely consumed marine food source in Indonesia and has the potential to serve as a vital nutritional resource. This study aimed to analyze the primary nutrient contents of anchovy, including protein, total fat, phosphorus, calcium, and iron levels. Nutritional composition analysis was conducted through laboratory testing using scientifically validated standard methods. The results were analyzed descriptively to provide an overview of the chemical composition of anchovy. The findings revealed that anchovy contains 31.5% protein, indicating its value as a rich source of animal protein. The total fat content was measured at 4.76%, suggesting a relatively low to moderate fat level. Furthermore, phosphorus content was recorded at 227.8 mg/kg, calcium at 2.45%, and iron at 36.1 mg/kg—all essential minerals for physiological functions. Based on these results, anchovy demonstrates strong potential as a highly nutritious local food source that could significantly contribute to meeting the community's nutritional needs.